A new EJG section entitled “Geographic Insights in Brief” - Panos Manetos; Alexandros Bartzokas-Tsiompras; Kostis C. Koutsopoulos (European Journal of Geography)
We are happy to announce a new European Journal of Geography (EJG) section titled ‘Geographic Insights in brief’. This initiative complements the new approach of EJG publishing (immediate publication of papers after the end of the review process) The short papers in this section will be published as part of each issue of the journal and will be reviewed only by the editorial team, in order to achieve fast dissemination of new and interesting ideas and applications. This section will accept two kinds of papers: First, papers announcing new ideas, breakthroughs and innovations in all Geographical areas that need to be immediately communicate to all geographers. The authors can later proceed to publish a fully developed traditional paper. Second, brief reports focusing on short, clear and pointed geographical research results and data. These shorter and more digestible items will help geographers to get a better understanding about specific spatial dimensions of environmental, social and economic phenomena and interactions that can feed an ongoing policy discussion with just a small amount of original visual analytics and geographical data. That is, present a smart and successive visualization or datasets, such as cartograms, mental maps, web-GIS platforms, real-time geographies and so on. This process provides new opportunities for intellectual communications and benefits for both researchers and practitioners to present new theoretical and empirical findings from new research and/or innovative geospatial applications.